2014
DOI: 10.1371/journal.pone.0113484
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Spo20 Membrane-Sensor Motif with Phosphatidic Acid and Other Anionic Lipids, and Influence of the Membrane Environment

Abstract: The yeast protein Spo20 contains a regulatory amphipathic motif that has been suggested to recognize phosphatidic acid, a lipid involved in signal transduction, lipid metabolism and membrane fusion. We have investigated the interaction of the Spo20 amphipathic motif with lipid membranes using a bioprobe strategy that consists in appending this motif to the end of a long coiled-coil, which can be coupled to a GFP reporter for visualization in cells. The resulting construct is amenable to in vitro and in vivo ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 42 publications
2
68
0
Order By: Relevance
“…PA, which promotes Lipin1 association with membranes (Ren et al, 2010), was not detected on nLDs or cLDs with a biosensor suggesting it is below the detection threshold or the biosensor is not sufficiently PA-specific, as was suggested previously (Horchani et al, 2014). Lipin1a was not detected on cLDs and associated with accumulation of DAG on cLDs in PML KO cells, which could reflect a partial block in TAG synthesis or increased TAG hydrolysis.…”
Section: Discussionmentioning
confidence: 59%
“…PA, which promotes Lipin1 association with membranes (Ren et al, 2010), was not detected on nLDs or cLDs with a biosensor suggesting it is below the detection threshold or the biosensor is not sufficiently PA-specific, as was suggested previously (Horchani et al, 2014). Lipin1a was not detected on cLDs and associated with accumulation of DAG on cLDs in PML KO cells, which could reflect a partial block in TAG synthesis or increased TAG hydrolysis.…”
Section: Discussionmentioning
confidence: 59%
“…GFP fusion proteins based on Spo20 51-91 have been established (Nakanishi, 2004) and optimized (Kassas et al, 2012;Zhang et al, 2014) to act as biosensors for PA in living cells. More recent studies by Antonny and coworkers reported that Spo20 does not efficiently distinguish between the anionic lipids, PA, PS and PIPs (Horchani et al, 2014). Instead, they found that the membrane binding of Spo20 51-91 relies on the negative charge density on the surface of the liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…The Q-SNARE Spo20 contains an amphipathic helix with a polybasic face that binds PA on prospores and the plasma membrane as a positive regulator of the protein (42). Its binding to PA depends on the presence of the acidic lipids PS and PI(4,5)P 2 (43). In mammalian cells syntaxin1 contains a PBR that binds to various PIs on lipid overlay experiments, whereas liposome binding shows that it preferentially binds to PA (44).…”
Section: Discussionmentioning
confidence: 99%